Prototype of Laminer and Turbulent Flow Learning Tools in the Fluid Mechanics Course at the Mechanical Engineering Study Program, Faculty of Engineering, Universitas Negeri Manado - Watuseke, Charles Benheart; Rompas, Parabelem Tinno Dolf; Manggopa, Hiskia Kamang (International Journal of Information Technology and Education, 2025)
In this study, the aim is to develop and analyze the performance of prototype laminar and turbulent flow learning tools in the Fluid Mechanics course in the Mechanical Engineering Study Program. The development of the tool was carried out to make it easier for students to understand the differences in flow characteristics through direct observation of changes in discharge, flow velocity, and Reynolds numbers. The research method used was an experiment by measuring discharge between 0.5–2 L/s on a transparent pipe with a diameter of 20 mm. Flow rate data is calculated based on actual discharge, while pressure is measured using differential manometers. Furthermore, the data were analyzed using the Reynolds number equation and the pressure loss theory (Darcy–Weisbach). Overall, the results show that the prototype is able to show the flow transition clearly, with the critical limit of the flow being at the average Reynolds number of about 2,200. At low discharge, the flow pattern indicates the stability of the laminar flow, while at high discharge vortex and velocity fluctuations are formed that mark turbulent flows. Pressure loss measurements also show a linear increase in laminar flow and a non-linear increase in turbulent flow, in line with fluid theory. These findings prove that the prototype developed is effective as a learning medium because it is able to visualize changes in flow regimes in real-time and provide a more interactive practicum experience.